From Inspiring Change to Directing Change: How Ethnographic Praxis Can Move beyond Research. Issue 1 (October 2015) - HOU, CAROLYN; HOLME, MADS
Abstract : This paper reflects on the evolving nature of ethnographic praxis in industry and argues that we must move beyond research and towards strategy in order to elevate our praxis, and to deliver real impact and value for our clients. Although this conversation is not new for the EPIC community, there has been a lack of models and examples – even in its tenth year – for how to do so. Taking a project with a medical device company that manufacturers voice prostheses for laryngectomees as a case study, we show how a team of social scientists used "Sensemaking" to determine a new commercial direction for innovation and to design a five‐year portfolio strategy for our client. In doing so, we illustrate how our praxis can do more than deliver research insights or design, but also act as the core foundation that defines business processes and strategy.